The efficacy of virtual reality in adults during puncture biopsy: A protocol of a systematic review and meta-analysis. - Xueling Qiu; Lukun Sun; Lu Tang; Xiaochen Jiang; Weifeng Wang; Fan Sun; Chenxi Sun; Tianyi Song (PLoS ONE)
Background Puncture biopsy is a primary method for obtaining tissue or cell samples from tumors for histopathological diagnosis. However, patients often experience pain, anxiety, and discomfort during the procedure. Virtual reality is a novel technology developed through advancements in computer skill, and it is utilized in healthcare as a cognitive approach to relieve pain and relaxation. However, there is controversy in published trials regarding the efficacy of virtual reality in adults during puncture biopsy. Therefore, a synthesis of objective and accurate data is needed to support the efficacy of virtual reality for pain relief during puncture biopsy in adults. Method and analysis To identify suitable randomized controlled trials, published literature in eight electronic databases will be searched, including PubMed, Web of Science, Cochrane Library, Scopus, EMBASE, Chinese National Knowledge Infrastructure (CNKI), Wan-fang Data, and Chinese Biomedical Database (CBM). The collected data will be consolidated and subjected to meta-analysis by using RevMan 5.4. Mean difference will describe the continuous variables. 95% confidence intervals (CI) will characterize the interval estimates. Model categories will be selected based on heterogeneity. The quality of the inclusion of randomized controlled trials in terms of methodological quality will be assessed by the Cochrane Risk of Bias Assessment Tool. Additionally, strength and certainty of the evidence will be assessed by the GRADE system. Discussion The following protocol delineates the fundamental process and methodology to be employed in a systematic review and meta-analysis of data pertaining to the efficacy of virtual reality in the context of adult puncture biopsy. The results of the study will furnish healthcare professionals with evidence-based clinical evidence, thereby facilitating sound clinical decision-making and yielding beneficial consequences for the clinical domain. Trial registration PROSPERO registration number: CRD42024539303.